Practical simulation method for determination of effective atomic number from Rayleigh to Compton scattering ratio by MCNP - Toker, Ozan; Bilmez, Bayram; Akcali, Ozgur; Toker, Melis Ozsahin; Icelli, Orhan (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Monte Carlo simulation of the Rayleigh/Compton scattering method for effective atomic number determination with MCNP (version 6.2) was proposed. As known, effective atomic numbers can be used for evaluating shielding behavior, in non-destructive analysis and medical imaging, especially for binary compounds with high precision. Various methods for the determination of effective atomic number are present in the literature, and they depend on different mathematical manipulations. For the first time, a simulation method was developed for the determination of effective atomic numbers of some compounds. Rayleigh to Compton scattering intensity ratios (R/C) of seven different pure elements (from Indium to Gadolinium) were determined with simulations. A straight line equation is fitted using R/C scattering intensity ratios of these seven elements. R/C values of five different compounds were also simulated. Thus, effective atomic numbers of these compounds were determined using the equation. The results of the simulation were compared with available experimental and theoretical results. The studied simulation method showed acceptable agreement with ZXCOM calculation results and acceptable results with the experimental study. This method is suitable to be used for almost every material type and quite insensitive to experimental details, such as material phase, thickness, etc. The simulation results are really encouraging and can be used to guide various experiments.
Keywords: Rayleigh to compton; Effective atomic number; Simulation; ZXCOM; MCNP 6.2; Chemistry; Nuclear Science & Technology; Physics